A Novel Reconfiguration Strategy of a Delta-Type Parallel Manipulator. (4th February 2016) - Balmaceda-Santamaría, Albert Lester; Castillo-Castaneda, Eduardo; Gallardo-Alvarado, Jaime
This work introduces a novel reconfiguration strategy for a Delta-type parallel robot. The robot at hand, whose patent is pending, is equipped with an intermediate mechanism that allows for modifying the operational Cartesian workspace. Furthermore, singularities of the robot may be ameliorated owing to the inherent kinematic redundancy introduced by four actuable kinematic joints. The velocity and acceleration analyses of the parallel manipulator are carried out by resorting to reciprocal-screw theory. Finally, the manipulability of the new robot is investigated based on the computation of the condition number associated with the active Jacobian matrix, a well-known procedure. The results obtained show improved performance of the robot introduced when compared with results generated for another Delta-type robot.